Japan's Stagnant Nineties : A Vector Autoregression Retrospective - Rendu, Christel (IMF Working Papers; Working Paper ;, 1999)
This paper uses a vector autoregression (VAR) approach to identify the driving forces of the growth slowdown in Japan during the 1990s. Negative shocks to both residential and nonresidential investment are shown to have been important determinants of the slowdown. Despite the collapse in asset prices, negative shocks to private consumption were relatively small. A surprising conclusion is that trends in public consumption had a dampening impact on activity in the 1990s. The VAR estimations do not support the counterfactual conjecture that activity in Japan would have been significantly weaker in the absence of the expansionary shift in fiscal policy.